Cohesion Devices in Relation to Quality of Engineering Studentsâ Genre-Based Writings - Manalu, Santi Agustina (Sebelas Maret University, 2016)
Writing skill is one of the four language skills in learning English in EFL context. In writing, cohesivedevices are used to establish the links among the ideas in a sentence and paragraph. This study was aimed atinvestigating IT Del engineering studentsâ use of cohesive devices in genre based writing and the relationshipbetween the number of cohesive devices used and writing quality. There were 30 writings selected out of 50compositions written by the engineering students at IT Del. The quantitative analysis was performed toexplore the results. The findings revealed that the students applied a variety of cohesive devices in theirEnglish compositions, among which reference category had the highest percentage, followed by lexical andconjunction categories. Furthermore, it was found that there is no significant relationship between the numberof cohesive ties used and the quality of writing. The results have some important implications for learningEnglish as a Foreign Language.